The impact of work autonomy on job satisfaction of academic staff: an empirical examination of government universities in Sri Lanka - Amarasena, T. S. M.; Ajward, A. R.; Haque, A. K. M. Ahasanul (2015)
This study intends to examine whether work autonomy impacts academic staff members’ job satisfaction of state universities in Sri Lanka. As the research approach, a quantitative approach was employed. In collecting data, a structured questionnaire was used to collect responses from fifteen government universities in Sri Lanka. The multi-stage stratified random sampling method was applied to select a representative sample; and 423 usable questionnaires deemed appropriate for analysis were selected. The validity and reliability tests indicated that the measurement scales met the acceptable standards. The t-test and One-way ANOVA results indicated that depending on the selected demographic factors, current working status, gender, age, and highest level of education the perception on work autonomy of the academic staff members in state universities in Sri Lanka differs. Nevertheless, it was found that marital status and number of children had no impact on the perception of work autonomy. In terms of the regression analysis conducted, it was found out that the work autonomy was a highly significant factor affecting the academic staff members’ overall job satisfaction of state universities in Sri Lanka. This finding is expected to have significant policy implications.